Magnetohydrodynamic With Embedded Particle-In-Cell Simulation of the Geospace Environment Modeling Dayside Kinetic Processes Challenge Event - Chen Yuxi; Tóth Gábor; Hietala Heli; Vines Sarah K; Zou Ying; Nishimura Yukitoshi; Silveira Marcos V D; Guo Zhifang; Lin Yu; Markidis Stefano (AMER GEOPHYSICAL UNION, 2025)
We use the magnetohydrodynamic (MHD) with embedded particle-in-cell model (MHD-EPIC) to study the Geospace Environment Modeling (GEM) dayside kinetic processes challenge event at 01:50-03:00 UT on 18 November 2015, when the magnetosphere was driven by a steady southward interplanetary magnetic field (IMF). In the MHD-EPIC simulation, the dayside magnetopause is covered by a PIC code so that the dayside reconnection is properly handled. We compare the magnetic fields and the plasma profiles of the magnetopause crossing with the MMS3 spacecraft observations. Most variables match the observations well in the magnetosphere, in the magnetosheath, and also during the current sheet crossing. The MHD-EPIC simulation produces flux ropes, and we demonstrate that some magnetic field and plasma features observed by the MMS3 spacecraft can be reproduced by a flux rope crossing event. We use an algorithm to automatically identify the reconnection sites from the simulation results. It turns out that there are usually multiple X-lines at the magnetopause. By tracing the locations of the X-lines, we find that the typical moving speed of the X-line endpoints is about 70 km/s, which is higher than but still comparable with the ground-based observations.